The Roma at a Secondary Education School: Between Selective Isolation and Full Nivelation - Žemaitėlytė-Ivanavičė, Ingrida (Acta Paedagogica Vilnensia, 2019)
[full article and abstract in Lithuanian; abstract in English] Constructing the research was tried to find out roma students’ perception of identity to school community and describe the successful experience in that context. It’s trying to consider who is the roma student at secondaryschool: the representative of ethic minority, the member of school community or another. His experience at schoool we should consider the problem or the success of achieved for a long period of time result? Which identity is formed within school community and how it influences behavior at school? Can we control this process and whether we have to do that? In order to find out how roma people percept their group, their identity, relationship with another-school culture and expression of this perception, research is based on ethnographic methodology, and students are observed in their daily learning and intercourse space-at school. Ethnographic research methodology has helped to reveal in which way the roma student is thinking (interview method) and how he is behaving himself (observation method) at secondary school. Research revealed that roma students’, studying in the main classes of the school, formation as student’s identity is taking place applying three different behavior models: 1) Demonstrative refusal to adopt a school culture (although it is well percepted ) and it’s ignoring is inherent to the first model; 2) Full school culture’s adoption, assimilation and levelling is inherent to the second model; 3) Having no decision and partial adoption of school culture and standarts : in one situation accepting the school culture and in others deliberately ignoring it. All these behavior models can be considered successful. Those students, who choose the second model and absolute leveling, achieve higher academic results and school community adoption. However, this group of students is most likely to lose their roma identity, they found new identity-following the rules, obeying authority, literate roma. The only question is this still the identity of roma? Meanwhile, roma, who reject integration in advance continue to cherish their ethnic group’s traditions, their choice of assimilation rejection we have to respect also. The most complicated question arises considering about students attributed to the third behavior model or undecided: it’s not clear whether the education system has to try for their supposed „salvation“ or allow to make decisions themselves naturally rising from dialogue with society.